ANALISIS NASKAH “KERETA KENCANA” KARYA W.S. RENDRA - Adinda, Adinda (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2015)
The text of Kereta Kencana is a text from WS. Rendra work taken from the original text Les Chaises by Eugene Ionesco. Kereta Kencana is written by WS. Rendra. It had been choosen as the creative process analysis study. This research is aimed how the creative process analyzed a drama text done through the research to produce a show art exhibition. Through this text this creative process is hoped to explain the way of work before it is showed.Keywords: theater text analysis, creative process